2012
DOI: 10.1111/gtc.12007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of the two proliferating cell nuclear antigens from the hyperthermophilic archaeon, Thermococcus kodakarensis

Abstract: The DNA sliding clamp is a multifunctional protein involved in cellular DNA transactions. In Archaea and Eukaryota, proliferating cell nuclear antigen (PCNA) is the sliding clamp. The ring-shaped PCNA encircles double-stranded DNA within its central hole and tethers other proteins on DNA. The majority of Crenarchaeota, a subdomain of Archaea, have multiple PCNA homologues, and they are capable of forming heterotrimeric rings for their functions. In contrast, most organisms in Euryarchaeota, the other major sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 42 publications
4
31
2
Order By: Relevance
“…It was found that the two proteins form homotrimers in solution with similar three-dimensional structures [57]. However, although both PCNA1 and PCNA2 stimulate the activity of PolB [57] and Fen1 (flap endonuclease 1) (Z. Li and Z. Kelman, unpublished work), PCNA1 is sufficient for cell viability ( [58], and T. Santangelo and Z. Kelman, unpublished work).…”
Section: Polymerase Accessory Proteinsmentioning
confidence: 99%
“…It was found that the two proteins form homotrimers in solution with similar three-dimensional structures [57]. However, although both PCNA1 and PCNA2 stimulate the activity of PolB [57] and Fen1 (flap endonuclease 1) (Z. Li and Z. Kelman, unpublished work), PCNA1 is sufficient for cell viability ( [58], and T. Santangelo and Z. Kelman, unpublished work).…”
Section: Polymerase Accessory Proteinsmentioning
confidence: 99%
“…Indeed, one of the two PCNA proteins in T. kodakarensis bound to Hef at IDR. The bound PCNA was PCNA1, which is essential for the viability of T. kodakarensis and is probably a regular member of the replisome (35). PCNA1 in the progressing replisome can stimulate recruitment of Hef when the replication fork stalls.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the gene for PCNA2 can be knocked out and the physiological function of PCNA2 has not been elucidated. Furthermore, many more molecules of PCNA1 exist as compared with PCNA2 (35). We analyzed only PCNA1 in this study, and will see the relationships between PCNA2 and Hef in our further works.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding for PCNA are present in all archaeal genomes and while the genomes of most euryarchaeota contain a single gene encoding PCNA, the genome of Thermococcus kodakarensis contains two genes encoding PCNA homologues (TK0535 and TK0582, encoding PCNA1 and PCNA2, respectively) (2022). It was found that both proteins form homotrimeric structures with characteristics similar to those of other archaeal and eukaryal PCNA proteins (20,23).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that both proteins form homotrimeric structures with characteristics similar to those of other archaeal and eukaryal PCNA proteins (20,23). Both proteins were also shown to support processive DNA synthesis by DNA polymerase B (PolB) and polymerase D (PolD) (2022). …”
Section: Introductionmentioning
confidence: 99%